2020
DOI: 10.1523/eneuro.0266-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Movement Representations during Human Reaching Could Be Preserved in Memory for at Least 850 ms

Abstract: Humans adapt to mechanical perturbations such as force fields during reaching within tens of trials. However, recent findings suggested that this adaptation may start within one single trial, i.e., online corrective movements can become tuned to the unanticipated perturbations within a trial. This was highlighted in previous works with a reaching experiment in which participants had to stop at a via-point (VP) located between the start and the goal. A force field was applied during the first and second parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 58 publications
(76 reference statements)
2
20
0
Order By: Relevance
“…Then we compared the EMG in baseline trials with the first trial in adaptation and readaptation blocks for each participant and found no significant difference (repeated measures ANOVA for PEC: F(2,30)=0.26;p=0.76, ;BF =24.31 and for DELT: F(2,30) =0.61, p=0.54, ; BF = 16.91, strong evidence for the null hypothesis that muscles activities are equal). This supports the argument that the better reach control in the first trial in readaptation blocks was not due to any co-contraction modulating the limb intrinsic properties, instead, it involved a feedback adaptation component that was described previously (Crevecoeur et al, 2020a; Mathew et al, 2020).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Then we compared the EMG in baseline trials with the first trial in adaptation and readaptation blocks for each participant and found no significant difference (repeated measures ANOVA for PEC: F(2,30)=0.26;p=0.76, ;BF =24.31 and for DELT: F(2,30) =0.61, p=0.54, ; BF = 16.91, strong evidence for the null hypothesis that muscles activities are equal). This supports the argument that the better reach control in the first trial in readaptation blocks was not due to any co-contraction modulating the limb intrinsic properties, instead, it involved a feedback adaptation component that was described previously (Crevecoeur et al, 2020a; Mathew et al, 2020).…”
Section: Resultssupporting
confidence: 89%
“…All extracted parameters from the very first relearning trials presented the features of more adapted movements. If we can demonstrate that there was no anticipation of the force field at the beginning of the readaptation phase, that is the washout was complete, then the improvement in the first relearning trials must correspond to an adaptation of online feedback control (Crevecoeur et al, 2020b, 2020a; Mathew et al, 2020). The foregoing analysis shows that it was indeed the case.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations